Teaching the brain to read : strategies for improving fluency, vocabulary, and comprehension - Willis, Judy. (Alexandria, VA : Association for Supervision and Curriculum Development, 2008)
Provides brain-based teaching strategies for improving phonemic awareness, reading skills, fluency, vocabulary, and comprehension.
Includes bibliographical references (p. 163-169) and index.
Professional
Keywords: Brain; Reading; Reading -- Physiological aspects; Brain; Reading; Reading -- Physiological aspects